DECONSTRUCTION OF SORI GUSTI POETRY ANTHOLOGY BY DARMANTO JATMAN - Rina Zuliana (Badan Pengembangan dan Pembinaan Bahasa, 2022)
This paper discussed the deconstruction of linguistic structures, forms, and contents in an antology of Sori Gusti's poems by Darmanto Jatman. The aim was to reveal the things behind the form and content of Sori Gusti's poetry text by using the strategy of reading Derrida's Deconstruction. The use of multilinguality in the text to decentering in the use of the concept of language, between local languages and foreign languages, as well as between other language opposition. The reversal and obscurity of the opposition of the language led to the reconciliation of culture represented in the text as a form of diversity. In terms of typography poetry, negation or obscurity of the center (decentering) through the use of the form of speech spoken by “aku lirik” as an inferior voice. At conventions generally speeches had a vertical concept, the speech of the leader to his people, then obscured by a horizontal concept (equivalent line). The vertical-horizontal conception was then formulated to reveal the political content behind the text, neo-imperialism of Orde Baru regim. AbstrakTulisan ini membahas dekonstruksi struktur linguistik, bentuk, dan isi dalam kumpulan puisi Sori Gusti karya Darmanto Jatman. Tujuannya untuk mengungkap hal ihwal di balik bentuk dan isi teks puisi Sori Gusti dengan menggunakan strategi pembacaan Dekonstruksi Derrida. Pemanfaatan multilingualitas dalam teks untuk meniadakan pusat (decentering) dalam penggunaan konsep bahasa, baik antara bahasa lokal dengan bahasa asing, maupun antaroposisi bahasa lainnya. Pembalikan dan pengaburan oposisi bahasa tersebut mengarah pada pendamaian budaya yang terepresentasi dalam teks sebagai bentuk keberagaman. Dari segi tipografi puisi dan peniadaan atau pengaburan pusat (decentering) melalui penggunaan bentuk pidato yang dituturkan oleh aku lirik sebagai suara inferior . Pada konvensi umumnya pidato memiliki konsep vertikal, tuturan pemimpin kepada rakyatnya, kemudian dikaburkan dengan konsep horisontal (garis setara). Konsepsi vertikal-horisontal kemudian diformulasikan untuk mengungkap muatan politis di balik teks, yakni neoimperialisme Orde Baru.